Naissance d’une nouvelle élite ottomane. Formation et trajectoires des médecins diplômés de Beyrouth à la fin du xixe siècle - Chantal Verdeil (Revue des Mondes Musulmans et de la Méditerranée)
At the end of the 19th century, two faculties of medicine were founded in Beirut. The Medical Department of the Syrian Protestant College was inaugurated in 1867 and the French Faculty of Medicine of the Saint-Joseph University of Beirut in 1883. Both were foreign institutions linked to missionaries. From their foundation until 1914, several hundred physicians graduated from these faculties. They belonged to the new elite of Ottoman society. Most of them were born in the Bilad al-Shâm or in Asia Minor. They belonged to families which were connected to French or American missionaries. Most of them made their careers in the Ottoman Empire. They held positions in the developing Ottoman health service, in the missionaries’ hospitals or in the foreign companies established in the Ottoman Empire.